2009
DOI: 10.1158/1078-0432.ccr-08-1282
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Epidermal Growth Factor Receptor by Selective Expansion of a 5′-End Regulatory Dinucleotide Repeat in Colon Cancer with Microsatellite Instability

Abstract: Purpose: The epidermal growth factor receptor (EGFR) is overexpressed in several tumor types, and its expression is influenced by the length of a 5 ¶-end microsatellite repeat (CA) n : the longer the repeat, the lower the expression. Dinucleotide repeats accumulate insertion/deletion types of mutations in tumors with microsatellite instability. We designed this study to estimate the occurrence of these mutations in EGFR(CA) n and their relevance in carcinogenesis of microsatellite instability^positive colon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
2
14
1
1
Order By: Relevance
“…EGFR protein expression was unrelated to tumour MMR status. This finding does not support a recent study that found elongation of a dinucleotide repeat in 55% of colon cancers with defective MMR, that was associated with significantly reduced EGFR mRNA levels (Baranovskaya et al, 2009). EGFR intensity as a continuous EGFR variable was significantly associated with shorter DFS and OS rates in a univariate analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…EGFR protein expression was unrelated to tumour MMR status. This finding does not support a recent study that found elongation of a dinucleotide repeat in 55% of colon cancers with defective MMR, that was associated with significantly reduced EGFR mRNA levels (Baranovskaya et al, 2009). EGFR intensity as a continuous EGFR variable was significantly associated with shorter DFS and OS rates in a univariate analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, elongation of a microsatellite repeat at the 5 0 UTR was found in colon cancers with defective MMR, but not in those with intact MMR (Baranovskaya et al, 2009), and elongation of this repeat was associated with downregulation of EGFR mRNA levels. Accordingly, we compared EGFR expression with MMR status in our study population.…”
Section: Phospho-egfr In Human Colon Cancers Rl Rego Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…53 The frequency of upregulation ranges anywhere from 25–90%, but EGFR downregulation is also known, and EFGR-negative tumors have been reported. 5255 Because EGFR positive tumors have been implicated in poor prognosis, we believe that EGFR may be a good marker to indicate prognosis and subsequent method of treatment. 56 …”
Section: Discussionmentioning
confidence: 99%
“…First, mammary and epidermoid tumor cells undergo growth arrest and apoptosis following EGF treatment (74,75). Second, mutations that decrease EGFR expression in a subset of colon and gastric tumors are associated with increased tumor progression (76). Finally, activating EGFR mutations in non-small cell lung cancer are associated with…”
Section: Discussionmentioning
confidence: 99%